A pre-lithiated silicon-oxygen-carbon material, silicon-oxygen-carbon-graphite composite material, and preparation method and application thereof
Through the pre-lithium silicone carbon material and silicon oxygen-carbon-graphite composite method, the problem of swelling the volume of lithium-ion battery negative materials in the charging and discharge process is solved, and the battery performance of high-efficiency and stable cycle is achieved.
Patent Information
- Application Number
- CN202111515287.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-13
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-12-13
AI Technical Summary
The volume expansion of existing lithium-ion battery anode materials during charging and discharging is severe, resulting in material separation, structural damage, reduced Coulomb efficiency and safety hazards.
Using prefabricated silicon oxygen carbon materials and silicon oxygen-carbon-graphite composite materials, mixed with Siox particles, graphite, conductive polymer fiber and lithium-containing compounds, sintering, and set carbon layer on the intermediate body to form a spherical shape The particles are rich in pore structure and conductive network.
It significantly improves the first charging and discharge efficiency of lithium -ion batteries and Kuron efficiency, stabilizes the cycle performance, reduces the deterioration of the polar interface caused by the volume effect, and has the characteristics of high -end effectiveness and long cycle.
Smart Images

Figure BDA0003406702650000181 
Figure BDA0003406702650000191
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a pre-lithiation silicon-oxygen-carbon material, a silicon-oxygen-carbon-graphite composite material, and a preparation method and application thereof. Background Art
[0002] With the continuous development of new energy technologies, the demand for lithium-ion secondary batteries with high safety, high energy density and long cycle life is becoming increasingly urgent. Lithium-ion secondary batteries are assembled from positive electrodes, negative electrodes, separators and electrolytes. The electrical performance of the battery is closely related to each part. The selection of positive and negative active materials will directly affect the final performance of the lithium-ion battery. Currently, the commercial battery negative electrode material is mainly graphite, but the theoretical specific capacity of graphite is low, at 372mAh / g, and it is difficult to further improve it, which greatly limits the development of lithium-ion batteries towards high energy density. Therefore, it is only a matter of time before traditional graphite materials are replaced by other materials with higher capacity.
[0003] Compared with graphite materials, silicon-based materials have significant capacity advantages. The theoretical specific capacity of silicon-based materials is 4200mAh / g, which is more than 10 times that of graphite materials. At the same time, silicon-based materials are abundant in sources and have relatively low processing costs, making them an ideal negative electrode material. However, as negative electrode materials for lithium-ion batteries, silicon-based materials also face the following challenges: pure silicon materials undergo serious volume changes during the charging and discharging process, with volume expansion reaching 300%, resulting in pulverization and separation between materials, and the destruction of the battery pole structure, which causes the capacity to decay rapidly; at the same time, the volume effect of silicon makes it difficult to form a stable SEI film, resulting in continuous consumption of lithium ions and electrolytes, and reduced coulombic efficiency; moreover, the conductivity of silicon materials themselves is poor, polarization is serious during the charging and discharging process, and the rate performance is poor. Lithium-ion batteries containing silicon-based negative electrode materials have hidden dangers in terms of aging and safety.
[0004] Composite materials formed by combining silicon-based materials with graphite materials can improve the performance of negative electrode materials to a certain extent. For example, CN112952054A discloses a method for preparing a silicon-based negative electrode material, the steps of which are as follows: S1, surface modification of silicon oxide raw material, the modification method including coating with a carbon source and / or ion doping of silicon oxide with a doping source; S2, mixing the carbon source, graphene and surface-modified silicon oxide into a slurry, drying, calcining, gas crushing and sieving to obtain a silicon-based capacity unit; S3, mixing the silicon-based capacity unit with a carbon-based material to obtain a silicon-based negative electrode material. CN109686957A discloses a method for preparing a composite negative electrode material, wherein a mixture of a SiO-based silicon-carbon composite negative electrode material precursor formed by SiO powder and carbon nanotubes, artificial graphite and asphalt is coated at high temperature in a coating furnace to obtain a composite negative electrode material, and the carbonization process of asphalt is used to improve the fusion of graphite and silicon materials. CN110844908A discloses a method for preparing a high-performance silicon-carbon-graphite composite negative electrode material for lithium-ion batteries, wherein an organic carbon source is dissolved in a solvent, and then nano-silicon particles are added and mixed uniformly, and flake graphite is added to the mixture for continuous vacuum-high pressure impregnation reaction and vacuum drying to obtain a silicon-carbon composite material precursor; the silicon-carbon composite material precursor is spheroidized, and then the surface is solid-phase coated, and finally the composite negative electrode material is obtained by sintering and screening. With the further development of lithium-ion batteries, there are still some problems in the use of silicon-based-carbon-based composite materials. For example, the silicon oxide particles coated with carbon are difficult to be evenly dispersed in the battery slurry due to their small particle size; in addition, the volume expansion problem of pure silicon materials is difficult to avoid. The volume expansion rate of silicon oxide is lower than that of pure silicon materials, but due to its own characteristics, a part of active lithium will be irreversibly consumed in the lithium insertion process to generate lithium silicate and lithium oxide, thereby showing a lower initial charge and discharge efficiency; at the same time, the current silicon-based-carbon-based composite materials are also difficult to improve the conductivity, and the lower ion mobility and electron migration rate are also key factors restricting its development.
[0005] Therefore, developing a negative electrode material with high capacity, good coulombic efficiency and stable cycle performance is the research focus in this field. Summary of the invention
[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a pre-lithiated silicon oxygen carbon material, a silicon oxygen carbon-graphite composite material and a preparation method and application thereof. The pre-lithiated silicon oxygen carbon material has a rich pore structure and a conductive network. The silicon oxygen carbon-graphite composite material containing the pre-lithiated silicon oxygen carbon material has rich internal pores, a stable structure, a high capacity, and good conductivity. It can be used as a negative electrode material to significantly improve the first-cycle coulombic efficiency and cycle performance of lithium-ion batteries.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a pre-lithiated silicon-oxygen-carbon material, the preparation method comprising the following steps:
[0009] (1) SiO x The particles, graphite, conductive polymer fibers and lithium-containing compounds are mixed and granulated to obtain a precursor;
[0010] (2) sintering the precursor obtained in step (1) to obtain an intermediate;
[0011] (3) Arranging a carbon layer on the intermediate obtained in step (2) to obtain the pre-lithiated silicon-oxygen-carbon material.
[0012] Wherein, 0<x<2, for example, x can be 0.1, 0.3, 0.5, 0.8, 1, 1.2, 1.5 or 1.8, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention will no longer exhaustively list the specific point values included in the range; preferably, the SiO x The particles are silicon oxide particles.
[0013] In the preparation method provided by the present invention, SiO x The particles are mixed with graphite, conductive polymer fibers, and lithium-containing compounds, and then sintered. A carbon layer is coated on the intermediate formed by sintering. The obtained pre-lithiated silicon oxygen carbon material is a spherical particle with rich pore structure and conductive network inside. While maintaining high capacity, the conductive performance, initial charge and discharge efficiency and coulomb efficiency of the material are improved, and SiO x The volume expansion provides space to accommodate the increase in the cycle performance.
[0014] Preferably, the SiO x The median particle size of the particles is 600-900nm, for example, it can be 620nm, 650nm, 680nm, 700nm, 720nm, 750nm, 780nm, 800nm, 820nm, 850nm or 880nm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and it is further preferably 750-850nm.
[0015] Preferably, the graphite is flake graphite.
[0016] As a preferred technical solution of the present invention, the graphite is flake graphite, which can be more evenly coated on SiO x On the particles, a pre-lithiated silicon-oxygen-carbon material with a spherical structure, good conductivity and rich internal pores is formed.
[0017] Preferably, the flake graphite has a diameter of 1-5 μm, for example, 1.2 μm, 1.5 μm, 1.8 μm, 2 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4 μm, 4.2 μm, 4.5 μm or 4.8 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 1.5-3 μm is further preferred.
[0018] Preferably, the graphite and SiO x The mass ratio of the particles is (1-3):1, for example, it can be 1.1:1, 1.3:1, 1.5:1, 1.7:1, 1.9:1, 2:1, 2.1:1, 2.3:1, 2.5:1, 2.7:1 or 2.9:1, and more preferably (1-2):1.
[0019] Preferably, the conductive polymer fiber includes any one of polyaniline fiber, polypyrrole fiber or polythiophene fiber, or a combination of at least two thereof.
[0020] Preferably, the diameter of the conductive polymer fiber is 0.05-1 μm, for example, it can be 0.06 μm, 0.08 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 0.95 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0021] Preferably, the aspect ratio of the conductive polymer fiber is 1.5-10, for example, it can be 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9 or 9.5, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and it is further preferably 2-3.
[0022] As a preferred technical solution of the present invention, the conductive polymer fiber is a nanofiber with a diameter of 0.05-1 μm and an aspect ratio of 1.5-10, which helps to form a rich linear conductive network inside the pre-lithiated silicon oxygen carbon material, thereby improving the conductive properties of the pre-lithiated silicon oxygen carbon material and improving its coulombic efficiency.
[0023] Preferably, the conductive polymer nanofibers and SiO xThe mass ratio of the particles is (1-1.5):1, for example, it can be 1.05:1, 1.1:1, 1.15:1, 1.2:1, 1.25:1, 1.3:1, 1.35:1, 1.4:1 or 1.45:1, etc.
[0024] Preferably, the lithium-containing compound is selected from any one of lithium oxide, lithium hydroxide or lithium salt or a combination of at least two thereof, and lithium salt is more preferably selected.
[0025] Preferably, the lithium salt includes any one of lithium carbonate, lithium acetate, lithium chloride, phenyl lithium or naphthyl lithium, or a combination of at least two thereof, and lithium carbonate is more preferred.
[0026] Preferably, the median particle size of the lithium salt is 100-500 nm, for example, it can be 120 nm, 150 nm, 180 nm, 200 nm, 220 nm, 250 nm, 280 nm, 300 nm, 320 nm, 350 nm, 380 nm, 400 nm, 420 nm, 450 nm or 480 nm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0027] Preferably, the lithium-containing compound and SiO x The mass ratio of the particles is (0.3-1.5):1, for example, it can be 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1 or 1.4:1, etc.
[0028] As a preferred technical solution of the present invention, the SiO x The mass ratio of particles, graphite, conductive polymer fibers and lithium-containing compounds is 1:(1-3):(1-1.5):(0.3-1.5). The four components cooperate with each other in a specific ratio, and are mixed and granulated and then sintered to form an intermediate, and a carbon layer is coated on the intermediate, so that the obtained pre-lithiation silicon oxygen carbon material has excellent conductivity, higher first-round coulomb efficiency and better cycle performance while maintaining high capacity. If the mass ratio of the components exceeds the above range, when the content of graphite and conductive polymer fibers is too low, it is impossible to form a rich pore structure and conductive network, resulting in the conductive properties and coulomb efficiency of the pre-lithiation silicon oxygen carbon material. Improvement is not obvious, and the spherical morphology after granulation is not obvious; when the content of graphite and conductive polymer fibers is too high, it will affect the capacity of the material; when the content of lithium-containing compounds is too low, it will affect the lithium supplement effect, and it is difficult to achieve an increase in the first-round coulomb efficiency, and there are fewer internal pores, making it difficult to alleviate the changes caused by the silicon-carbon volume effect.
[0029] Preferably, the mixing method in step (1) includes wet mixing.
[0030] Preferably, the solvent for wet mixing is an organic solvent.
[0031] Preferably, the organic solvent comprises ethanol and / or isopropanol.
[0032] Preferably, the granulation method in step (1) is spray drying.
[0033] Preferably, the granulation temperature in step (1) is 60-110°C, for example, it can be 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C or 105°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0034] Preferably, the sintering temperature in step (2) is 700-1000°C, for example, it can be 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C, 900°C, 920°C, 950°C or 980°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0035] Preferably, the sintering time in step (2) is 1-8 h, for example, it can be 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h or 7.5 h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and it is further preferably 2-6 h.
[0036] Preferably, the sintering in step (2) is carried out in a protective atmosphere.
[0037] Preferably, the protective atmosphere is an inert atmosphere, including a nitrogen atmosphere and / or an argon atmosphere.
[0038] Preferably, the method for providing the carbon layer in step (3) includes a gas phase carbon coating method, a liquid phase carbon coating method or a solid phase carbon coating method.
[0039] Preferably, the carbon source of the gas phase carbon coating method includes any one of acetylene, ethylene, methane, ethane, propane or butane, or a combination of at least two thereof.
[0040] Preferably, the coating temperature of the vapor phase carbon coating method is 700-1200°C, for example, it can be 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C, 900°C, 920°C, 950°C, 980°C, 1000°C, 1050°C, 1100°C or 1150°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 750-1000°C is further preferred.
[0041] Preferably, the coating time of the vapor phase carbon coating method is 0.5-3h, for example, it can be 0.75h, 1h, 1.25h, 1.5h, 1.75h, 2h, 2.25h, 2.5h or 2.75h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0042] Preferably, the mass percentage of the carbon layer in the pre-lithiation silicon oxygen carbon material is 1-10%, for example, it can be 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9% or 9.5%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and it is further preferably 3-8%.
[0043] In a second aspect, the present invention provides a pre-lithiated silicon oxycarbon material, wherein the pre-lithiated silicon oxycarbon material is prepared by the preparation method described in the first aspect.
[0044] Preferably, the pre-lithiated silicon oxycarbon material is in the form of spherical particles.
[0045] Preferably, the median particle size of the pre-lithiation silicon oxycarbon material is 8-20 μm, for example, it can be 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm or 19 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0046] In a third aspect, the present invention provides a silicon oxygen carbon-graphite composite material, wherein the silicon oxygen carbon-graphite composite material comprises a combination of the pre-lithiated silicon oxygen carbon material as described in the second aspect and graphite.
[0047] Preferably, the graphite is secondary graphite particles.
[0048] Preferably, the ratio of the median particle size of the pre-lithiated silicon oxygen carbon material to the median particle size of the graphite secondary particles is 1:(1.25-2.5), for example, it can be 1:1.3, 1:1.35, 1:1.4, 1:1.45, 1:1.5, 1:1.55, 1:1.6, 1:1.65, 1:1.7, 1:1.8, 1:1.9, 1:2.0, 1:2.1, 1:2.2, 1:2.3 or 1:2.4, etc., and is further preferably 1:(1.25-2.0).
[0049] As a preferred technical solution of the present invention, the ratio of the median particle size of the pre-lithiated silicon oxygen carbon material to the graphite secondary particles is 1: (1.25-2.0), and the two cooperate with each other to build a stable structure. The pre-lithiated silicon oxygen carbon material is concentrated inside the electrode, and the spherical particles formed have abundant pores and a linear conductive network inside, which gives the material excellent conductive properties, specific capacity and coulombic efficiency, and is SiO x The volume expansion provides space for accommodation, thereby reducing the deterioration of the electrode interface caused by the volume effect, showing excellent cycle performance, and has the performance advantages of high first efficiency and long cycle.
[0050] Preferably, the median particle size of the graphite secondary particles is 15-35 μm, for example, it can be 15.5 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, 30 μm, 31 μm, 32 μm, 33 μm or 34 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0051] Preferably, the mass ratio of the pre-lithiated silicon oxygen carbon material to graphite is 1:(1-3), for example, it can be 1:1.1, 1:1.3, 1:1.5, 1:1.7, 1:1.9, 1:2, 1:2.1, 1:2.3, 1:2.5, 1:2.7 or 1:2.9, etc.
[0052] Preferably, the specific surface area of the silicon oxygen carbon-graphite composite material is 1.8-2.5m 2 / g, for example, 1.85m 2 / g, 1.9m 2 / g, 1.95m 2 / g, 2.0m 2 / g, 2.05m 2 / g, 2.1m 2 / g, 2.15m 2 / g, 2.2m 2 / g, 2.25m 2 / g, 2.3m 2 / g, 2.35m 2 / g, 2.4m 2 / g or 2.45m 2 / g, as well as specific point values between the above point values. Due to space limitations and for the sake of brevity, the present invention no longer exhaustively lists the specific point values included in the range.
[0053] Preferably, the powder resistivity of the silicon oxygen carbon-graphite composite material is 1.0-20.0 μΩ / cm, for example, it can be 3.0 μΩ / cm, 5.0 μΩ / cm, 7.0 μΩ / cm, 9.0 μΩ / cm, 10.0 μΩ / cm, 11.0 μΩ / cm, 13.0 μΩ / cm, 15.0 μΩ / cm, 17.0 μΩ / cm or 19.0 μΩ / cm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0054] In a fourth aspect, the present invention provides a method for preparing the silicon oxygen carbon-graphite composite material as described in the third aspect, the preparation method comprising: uniformly mixing the pre-lithiated silicon oxygen carbon material with graphite to obtain the silicon oxygen carbon-graphite composite material.
[0055] Preferably, the mixing is performed in a high-speed mixer.
[0056] Preferably, the mixing rotation speed is 500-2000 rpm, for example, it can be 600 rpm, 800 rpm, 1000 rpm, 1100 rpm, 1300 rpm, 1500 rpm, 1700 rpm or 1900 rpm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0057] Preferably, the mixing time is 5-30 min, for example, it can be 6 min, 8 min, 10 min, 12 min, 15 min, 18 min, 20 min, 22 min, 25 min or 28 min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and it is further preferably 10-20 min.
[0058] In a fifth aspect, the present invention provides a negative electrode active material, wherein the negative electrode active material comprises the pre-lithiation silicon oxygen carbon material as described in the second aspect and / or the silicon oxygen carbon-graphite composite material as described in the third aspect.
[0059] In a sixth aspect, the present invention provides a lithium-ion battery, comprising a negative electrode, wherein the negative electrode comprises at least one of the pre-lithiated silicon-oxygen-carbon material as described in the second aspect, the silicon-oxygen-carbon-graphite composite material as described in the third aspect, and the negative electrode active material as described in the fifth aspect.
[0060] Compared with the prior art, the present invention has the following beneficial effects:
[0061] The pre-lithiation silicon oxygen carbon material provided by the present invention has a spherical particle morphology, and contains a rich pore structure and a conductive network inside, which improves the conductive performance, initial charge and discharge efficiency and coulombic efficiency of the material while maintaining a high capacity. The pre-lithiation silicon oxygen carbon material and graphite cooperate with each other, and the obtained silicon oxygen carbon-graphite composite material has a stable structure, rich pores and a three-dimensional conductive network inside, giving the material excellent conductive performance, specific capacity and coulombic efficiency, and is SiO x The volume expansion provides an accommodating space, thereby reducing the deterioration of the electrode interface caused by the volume effect, and exhibiting excellent cycle performance; the silicon oxygen carbon-graphite composite material as the negative electrode active material of the lithium ion battery has a specific capacity of ≥600mAh / g, a first-cycle coulomb efficiency of 88.7-92.5%, a cycle retention rate of ≥91.2%, and an expansion rate of ≤91%. It has the performance characteristics of high first efficiency and long cycle, and meets the high performance requirements of lithium ion batteries for negative electrode materials. DETAILED DESCRIPTION
[0062] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0063] In the present invention, the particle size (median particle size D 50 ) and flake diameter can be obtained by testing with a laser particle size analyzer, or by measuring the morphology with a scanning electron microscope, and the particle size or flake diameter can be calculated from the figure.
[0064] In the following preparation examples and embodiments, all median particle sizes D 50 The particle size and flake diameter were measured by laser particle size analyzer (Mastersizer 3000).
[0065] Preparation Example 1
[0066] A pre-lithiated silicon-oxygen-carbon material and a preparation method thereof, the preparation method comprising the following steps:
[0067] (1) 200g median particle size (D 50) is 800nm silicon oxide particles, 300g of flake graphite with a sheet diameter of 1μm, 200g of polyaniline fiber (aspect ratio of 5.0, diameter of 200nm) and 160g of lithium carbonate (nanoscale), put into ethanol solvent, stir and disperse, adjust the solid content of the mixed slurry to 25%, then spray dry at a drying temperature of 90°C, and granulate to obtain a precursor;
[0068] (2) transferring the precursor obtained in step (1) into a box furnace, introducing an inert gas, heating the temperature to 800° C. at a heating rate of 200° C. / h, keeping the temperature for 4 h, and cooling to obtain an intermediate;
[0069] (3) The intermediate obtained in step (2) is placed in a rotary kiln, nitrogen is introduced, and the temperature is increased to 900° C. at a heating rate of 200° C. / h, with an acetylene flow rate of 90 L / h and a nitrogen flow rate of 180 L / h. The mixture is kept warm for 1 h and naturally cooled to room temperature to obtain a spherical pre-lithiated silicon-oxygen-carbon material having a median particle size of 11.1 μm.
[0070] Preparation Example 2
[0071] A pre-lithiated silicon-oxygen-carbon material and a preparation method thereof, the preparation method comprising the following steps:
[0072] (1) 200g D 50 Silica particles with a particle size of 600 nm, 400 g of flake graphite with a sheet diameter of 2 μm, 250 g of polyaniline fiber (aspect ratio of 5.0, diameter of 200 nm) and 120 g of lithium carbonate are put into an ethanol solvent and stirred and dispersed, and the solid content of the mixed slurry is adjusted to 25%, followed by spray drying at a drying temperature of 90° C., and granulation to obtain a precursor;
[0073] (2) transferring the precursor obtained in step (1) into a box furnace, introducing an inert gas, heating the temperature to 900° C. at a heating rate of 200° C. / h, keeping the temperature for 2 h, and cooling to obtain an intermediate;
[0074] (3) The intermediate obtained in step (2) is placed in a rotary kiln, nitrogen is introduced, and the temperature is increased to 800° C. at a heating rate of 200° C. / h, with an acetylene flow rate of 90 L / h and a nitrogen flow rate of 180 L / h. The mixture is kept warm for 2 h and naturally cooled to room temperature to obtain a spherical pre-lithiated silicon-oxygen-carbon material having a median particle size of 12.9 μm.
[0075] Preparation Example 3
[0076] A pre-lithiated silicon-oxygen-carbon material and a preparation method thereof, the preparation method comprising the following steps:
[0077] (1) 200g D 50Silica particles with a particle size of 900 nm, 200 g of flake graphite with a sheet diameter of 5 μm, 200 g of polyaniline fiber (aspect ratio of 5.0, diameter of 200 nm) and 80 g of lithium carbonate are put into an ethanol solvent and dispersed by stirring, and the solid content of the mixed slurry is adjusted to 25%, followed by spray drying at a drying temperature of 90° C., and granulation to obtain a precursor;
[0078] (2) transferring the precursor obtained in step (1) into a box furnace, introducing an inert gas, heating the temperature to 700° C. at a heating rate of 200° C. / h, keeping the temperature for 6 h, and obtaining an intermediate after cooling;
[0079] (3) The intermediate obtained in step (2) is placed in a rotary kiln, nitrogen is introduced, and the temperature is increased to 1000° C. at a heating rate of 200° C. / h, with an acetylene flow rate of 90 L / h and a nitrogen flow rate of 180 L / h. The mixture is kept warm for 0.5 h and naturally cooled to room temperature to obtain a spherical pre-lithiated silicon-oxygen-carbon material having a median particle size of 19.3 μm.
[0080] Preparation Example 4
[0081] A pre-lithiated silicon-oxygen-carbon material and a preparation method thereof, the preparation method comprising the following steps:
[0082] (1) 200g D 50 Silica particles with a particle size of 800 nm, 600 g of flake graphite with a sheet diameter of 1 μm, 200 g of polyaniline fiber (aspect ratio of 5.0, diameter of 200 nm) and 200 g of lithium carbonate are put into an ethanol solvent and dispersed by stirring, and the solid content of the mixed slurry is adjusted to 25%, followed by spray drying at a drying temperature of 90° C., and granulation to obtain a precursor;
[0083] (2) transferring the precursor obtained in step (1) into a box furnace, introducing an inert gas, heating the temperature to 800° C. at a heating rate of 200° C. / h, keeping the temperature for 4 h, and cooling to obtain an intermediate;
[0084] (3) The intermediate obtained in step (2) is placed in a rotary kiln, nitrogen is introduced, and the temperature is increased to 900° C. at a heating rate of 200° C. / h, with an acetylene flow rate of 90 L / h and a nitrogen flow rate of 180 L / h. The mixture is kept warm for 3 h and naturally cooled to room temperature to obtain a spherical pre-lithiated silicon-oxygen-carbon material having a median particle size of 15.7 μm.
[0085] Preparation Example 5
[0086] A pre-lithiated silicon-oxygen-carbon material and a preparation method thereof, the preparation method comprising the following steps:
[0087] (1) 200g D 50Silica particles with a particle size of 800 nm, 300 g of flake graphite with a sheet size of 2 μm, 300 g of polyaniline fiber and 180 g of lithium carbonate are put into an ethanol solvent and dispersed by stirring, and the solid content of the mixed slurry is adjusted to 25%, and then spray-dried at a drying temperature of 90° C. to obtain a precursor by granulation;
[0088] (2) transferring the precursor obtained in step (1) into a box furnace, introducing an inert gas, heating the temperature to 800° C. at a heating rate of 200° C. / h, keeping the temperature for 4 h, and cooling to obtain an intermediate;
[0089] (3) The intermediate obtained in step (2) is placed in a rotary kiln, nitrogen is introduced, and the temperature is increased to 900° C. at a heating rate of 200° C. / h, with an acetylene flow rate of 90 L / h and a nitrogen flow rate of 180 L / h. The mixture is kept warm for 1 h and naturally cooled to room temperature to obtain a spherical pre-lithiated silicon-oxygen-carbon material having a median particle size of 13.2 μm.
[0090] Comparative Preparation Example 1
[0091] A pre-lithiated silicon-oxygen-carbon material and a preparation method thereof, the preparation method comprising the following steps:
[0092] (1) 200g D 50 Silica particles with a particle size of 800 nm, 300 g of flake graphite with a sheet size of 1 μm, and 160 g of lithium carbonate are put into an ethanol solvent and dispersed by stirring, and the solid content of the mixed slurry is adjusted to 25%, and then spray-dried at a drying temperature of 90° C. to granulate to obtain a precursor;
[0093] (2) transferring the precursor obtained in step (1) into a box furnace, introducing an inert gas, heating the temperature to 800° C. at a heating rate of 200° C. / h, keeping the temperature for 4 h, and cooling to obtain an intermediate;
[0094] (3) The intermediate obtained in step (2) is placed in a rotary kiln, nitrogen is introduced, and the temperature is increased to 900° C. at a heating rate of 200° C. / h, with an acetylene flow rate of 90 L / h and a nitrogen flow rate of 180 L / h. The mixture is kept warm for 1 h and naturally cooled to room temperature to obtain a spherical pre-lithiated silicon-oxygen-carbon material with a median particle size of 3.1 μm.
[0095] Comparative Preparation Example 2
[0096] A pre-lithiated silicon-oxygen-carbon material and a preparation method thereof, the preparation method comprising the following steps:
[0097] (1) 200g D 50Silica particles with a particle size of 800 nm, 300 g of flake graphite with a sheet size of 1 μm, 200 g of polyaniline (molecular weight ≥ 15000, manufacturer Shanghai Aladdin) and 160 g of lithium carbonate are put into an ethanol solvent and stirred and dispersed, and the solid content of the mixed slurry is adjusted to 25%, followed by spray drying at a drying temperature of 90° C., and granulation to obtain a precursor;
[0098] (2) transferring the precursor obtained in step (1) into a box furnace, introducing an inert gas, heating the temperature to 800° C. at a heating rate of 200° C. / h, keeping the temperature for 4 h, and cooling to obtain an intermediate;
[0099] (3) The intermediate obtained in step (2) is placed in a rotary kiln, nitrogen is introduced, and the temperature is increased to 900° C. at a heating rate of 200° C. / h, with an acetylene flow rate of 90 L / h and a nitrogen flow rate of 180 L / h. The mixture is kept warm for 1 h and naturally cooled to room temperature to obtain a spherical pre-lithiated silicon-oxygen-carbon material having a median particle size of 12.1 μm.
[0100] Comparative Preparation Example 3
[0101] A pre-lithiated silicon-oxygen-carbon material and a preparation method thereof, the preparation method comprising the following steps:
[0102] (1) 200g D 50 Silica particles with a particle size of 800 nm, 200 g of polyaniline fibers and 160 g of lithium carbonate are put into an ethanol solvent and stirred and dispersed, and the solid content of the mixed slurry is adjusted to 25%, and then spray-dried at a drying temperature of 90° C. to granulate to obtain a precursor;
[0103] (2) transferring the precursor obtained in step (1) into a box furnace, introducing an inert gas, heating the temperature to 800° C. at a heating rate of 200° C. / h, keeping the temperature for 4 h, and cooling to obtain an intermediate;
[0104] (3) The intermediate obtained in step (2) is placed in a rotary kiln, nitrogen is introduced, and the temperature is increased to 900° C. at a heating rate of 200° C. / h, with an acetylene flow rate of 90 L / h and a nitrogen flow rate of 180 L / h. The mixture is kept warm for 1 h and naturally cooled to room temperature to obtain a spherical pre-lithiated silicon-oxygen-carbon material having a median particle size of 6.7 μm.
[0105] Comparative Preparation Example 4
[0106] A pre-lithiated silicon-oxygen-carbon material and a preparation method thereof, the preparation method comprising the following steps:
[0107] (1) 200g D 50Silica particles with a particle size of 800 nm and 160 g of lithium carbonate are put into an ethanol solvent and dispersed by stirring, and the solid content of the mixed slurry is adjusted to 25%, and then spray-dried at a drying temperature of 90° C. to obtain a precursor by granulation;
[0108] (2) transferring the precursor obtained in step (1) into a box furnace, introducing an inert gas, heating the temperature to 800° C. at a heating rate of 200° C. / h, keeping the temperature for 4 h, and cooling to obtain an intermediate;
[0109] (3) The intermediate obtained in step (2) is placed in a rotary kiln, nitrogen is introduced, and the temperature is increased to 900° C. at a heating rate of 200° C. / h, with an acetylene flow rate of 90 L / h and a nitrogen flow rate of 180 L / h. The mixture is kept warm for 1 h and naturally cooled to room temperature to obtain a spherical pre-lithiated silicon-oxygen-carbon material with a median particle size of 2.2 μm.
[0110] Example 1
[0111] A silicon oxygen carbon-graphite composite material, comprising 300 g of pre-lithiated silicon oxygen carbon material (Preparation Example 1, D 50 Particle size is 11.1 μm) and 600 g of artificial graphite secondary particles (D 50 The particle size is 17.8 μm); the preparation method is as follows:
[0112] 300 g of pre-lithiated silicon-oxygen-carbon material (Preparation Example 1) and 600 g of artificial graphite secondary particles were placed in a high-speed mixer and mixed for 15 min at a speed of 1000 rpm to obtain the silicon-oxygen-carbon-graphite composite material.
[0113] Example 2
[0114] A silicon oxygen carbon-graphite composite material, comprising 300 g of pre-lithiated silicon oxygen carbon material (Preparation Example 2, D 50 Particle size is 12.9 μm) and 500 g of artificial graphite secondary particles (D 50 The particle size is 23.5 μm); the preparation method is as follows:
[0115] 300 g of pre-lithiated silicon-oxygen-carbon material (Preparation Example 2) and 500 g of artificial graphite secondary particles were placed in a high-speed mixer and mixed for 15 min at a speed of 1000 rpm to obtain the silicon-oxygen-carbon-graphite composite material.
[0116] Example 3
[0117] A silicon oxygen carbon-graphite composite material, comprising 300 g of pre-lithiated silicon oxygen carbon material (Preparation Example 3, D 50 Particle size is 19.3 μm) and 500 g of artificial graphite secondary particles (D 50 The particle size is 25.4 μm); the preparation method is as follows:
[0118] 300 g of pre-lithiated silicon-oxygen-carbon material (Preparation Example 3) and 500 g of artificial graphite secondary particles were placed in a high-speed mixer and mixed for 15 min at a speed of 1000 rpm to obtain the silicon-oxygen-carbon-graphite composite material.
[0119] Example 4
[0120] A silicon-oxygen-carbon-graphite composite material, comprising 300 g of pre-lithiated silicon-oxygen-carbon material (Preparation Example 4, D 50 Particle size is 15.7 μm) and 600 g of artificial graphite secondary particles (D 50 The particle size is 23.5 μm); the preparation method is as follows:
[0121] 300 g of pre-lithiated silicon-oxygen-carbon material (Preparation Example 4) and 600 g of artificial graphite secondary particles were placed in a high-speed mixer and mixed for 15 min at a speed of 1000 rpm to obtain the silicon-oxygen-carbon-graphite composite material.
[0122] Example 5
[0123] A silicon oxygen carbon-graphite composite material, comprising 300 g of pre-lithiated silicon oxygen carbon material (Preparation Example 5, D 50 Particle size is 13.2 μm) and 600 g of artificial graphite secondary particles (D 50 The particle size is 25.4 μm); the preparation method is as follows:
[0124] 300 g of pre-lithiated silicon-oxygen-carbon material (Preparation Example 5) and 600 g of artificial graphite secondary particles were placed in a high-speed mixer and mixed for 15 min at a speed of 1000 rpm to obtain the silicon-oxygen-carbon-graphite composite material.
[0125] Example 6
[0126] A silicon oxygen carbon-graphite composite material, which differs from Example 1 only in that the D of the artificial graphite secondary particles is 50 The particle size is 7.7 μm; the dosage of the components and the preparation method are the same as those in Example 1.
[0127] Example 7
[0128] A silicon oxygen carbon-graphite composite material, which differs from Example 1 only in that the D of the artificial graphite secondary particles is 50 The particle size is 34.3 μm; the dosage of the components and the preparation method are the same as those in Example 1.
[0129] Comparative Example 1
[0130] A silicon oxygen carbon-graphite composite material, which differs from Example 1 only in that the pre-lithiated silicon oxygen carbon material is the pre-lithiated silicon oxygen carbon material (D 50 The particle size is 3.1 μm); the dosage of the components and the preparation method are the same as those in Example 1.
[0131] Comparative Example 2
[0132] A silicon oxygen carbon-graphite composite material, which differs from Example 1 only in that the pre-lithiated silicon oxygen carbon material is the pre-lithiated silicon oxygen carbon material (D 50 The particle size is 12.1 μm); the dosage of the components and the preparation method are the same as those in Example 1.
[0133] Comparative Example 3
[0134] A silicon oxygen carbon-graphite composite material, which differs from Example 1 only in that the pre-lithiated silicon oxygen carbon material is the pre-lithiated silicon oxygen carbon material (D 50 The particle size is 6.7 μm); the dosage of the components and the preparation method are the same as those in Example 1.
[0135] Comparative Example 4
[0136] A silicon oxygen carbon-graphite composite material, which differs from Example 1 only in that the pre-lithiated silicon oxygen carbon material is the pre-lithiated silicon oxygen carbon material (D 50 The particle size is 2.2 μm); the dosage of the components and the preparation method are the same as those in Example 1.
[0137] Comparative Example 5
[0138] A silicon oxygen carbon-graphite composite material, which differs from Example 1 only in that the pre-lithiated silicon oxygen carbon material is the pre-lithiated silicon oxygen carbon material (D 50 The particle size is 3.1 μm), the D 50 The particle size is 5.1 μm; the dosage of the components and the preparation method are the same as those in Example 1.
[0139] Comparative Example 6
[0140] A silicon oxygen carbon-graphite composite material, which differs from Example 1 only in that the pre-lithiated silicon oxygen carbon material is the pre-lithiated silicon oxygen carbon material (D 50 The particle size is 6.7 μm), the D 50 The particle size is 10.7 μm; the dosage of the components and the preparation method are the same as those in Example 1.
[0141] Comparative Example 7
[0142] A silicon oxygen carbon-graphite composite material, which differs from Example 1 only in that the pre-lithiated silicon oxygen carbon material is the pre-lithiated silicon oxygen carbon material (D 50 The particle size is 2.2 μm), the D 50 The particle size is 3.6 μm; the dosage of the components and the preparation method are the same as those in Example 1.
[0143] The properties of the silicon oxygen carbon-graphite composite materials provided in Test Examples 1-7 and Comparative Examples 1-7 are as follows:
[0144] (1) Powder resistivity: A four-probe powder resistance tester is used to test the powder resistivity.
[0145] (2) Specific surface area: The specific surface area was tested using a specific surface area analyzer.
[0146] (3) Electrochemical performance: The silicon-oxygen-carbon-graphite composite materials provided in Examples 1-7 and Comparative Examples 1-7 were used as negative electrode active materials to assemble lithium-ion batteries, and the specific methods were as follows:
[0147] The negative electrode active material, binder (polyvinylidene fluoride, PVDF), and conductive agent (Super-P) were mixed in a mass ratio of 70:15:15, and N-methylpyrrolidone (NMP) was added as a solvent to prepare a slurry, which was coated on a copper foil, and vacuum dried and rolled to prepare a negative electrode sheet; a metal lithium sheet was used as a counter electrode, and a 1mol / L LiPF6 three-component mixed solvent (ethylene carbonate EC: dimethyl carbonate DMC: ethyl methyl carbonate EMC = 1:1:1, volume ratio) was used as an electrolyte, and a polypropylene microporous membrane was used as a separator. The button battery was assembled into a CR2032 button cell in a glove box filled with inert gas. The charge and discharge test of the button cell was carried out on the LANHE battery test system of Wuhan Landian Electronics Co., Ltd., at room temperature, 0.1C constant current charge and discharge, and the charge and discharge voltage was limited to 0.005-1.5V.
[0148] The volume expansion rate of the material is tested and calculated using the following method: expansion rate = 100% × (pole sheet thickness after 50 cycles - pole sheet thickness before cycles) / (pole sheet thickness before cycles - copper foil thickness).
[0149] The test results are shown in Table 1:
[0150] Table 1
[0151]
[0152]
[0153] It can be seen that the present invention compounds a specific pre-lithiation silicon oxygen carbon material with graphite, and builds a stable structure through the particle size ratio of the two, so that the structure of the silicon oxygen carbon-graphite composite material is stable, and there are abundant pores and a three-dimensional conductive network inside. As a negative electrode active material, it makes the specific capacity ≥600mAh / g, which is 600-700mAh / g, the first-cycle coulomb efficiency is 88.7-92.5%, the cycle retention rate is 91.2-96.2%, and the expansion rate is 59-91%, showing excellent conductivity, specific capacity and coulomb efficiency, reducing the deterioration of the electrode interface caused by the volume effect, and showing excellent cycle performance.
[0154] Combining the test results of Example 1 with those of Examples 6-7, it can be seen that if the ratio of the median particle size of the pre-lithiation silicon oxygen carbon material to the graphite exceeds the preferred range of 1: (1.25-2.5) of the present invention, the structural stability of the material will be reduced, the first-cycle reversible capacity and the first-cycle coulombic efficiency will be reduced, the expansion rate will be increased, and the cycle capacity retention rate will be reduced.
[0155] The pre-lithiation silicon-oxygen-carbon materials in Comparative Examples 1-4 do not use the combination of silicon oxide particles, graphite, conductive polymer fibers, and lithium-containing compounds defined in the present invention, resulting in the pre-lithiation silicon-oxygen-carbon materials being unable to obtain a rich pore structure and conductive network, and it is difficult to meet the particle size ratio of the pre-lithiation silicon-oxygen-carbon material to graphite (Comparative Examples 1, 3, and 4), and thus being unable to construct a stable structure, thereby deteriorating the conductivity of the material, and causing low specific capacity and first-cycle coulomb efficiency. After 50 cycles, severe volume expansion and capacity attenuation occur, and the cycle performance requirements of lithium-ion batteries cannot be met. Moreover, even if the median particle size ratio of the aforementioned pre-lithiation silicon-oxygen-carbon material to the secondary graphite particles meets the ratio range of 1: (1.25-2.5) (Comparative Examples 2, 5, 6, and 7), due to the poor conductivity and efficiency of the pre-lithiation silicon-oxygen-carbon material, severe expansion, the negative electrode active material is also unable to meet the first efficiency and cycle requirements of lithium-ion batteries.
[0156] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate a pre-lithiation silicon oxygen carbon material, silicon oxygen carbon-graphite composite material and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a pre-lithiated silicon-oxygen-carbon material, characterized in that: The preparation method comprises the following steps: (1) SiO x The particles, graphite, conductive polymer fibers and lithium-containing compounds are mixed and granulated to obtain a precursor; 0<x<2; (2) sintering the precursor obtained in step (1) to obtain an intermediate; (3) providing a carbon layer on the intermediate obtained in step (2) to obtain the pre-lithiated silicon-oxygen-carbon material; The conductive polymer fibers are nanofibers, so that a linear conductive network is formed inside the pre-lithiated silicon oxygen carbon material; The conductive polymer fiber has a diameter of 0.05-1 μm and an aspect ratio of 1.5-10.
2. The preparation method according to claim 1, characterized in that: The SiO x The median particle size of the particles is 600-900 nm.
3. The preparation method according to claim 1, characterized in that: The graphite is flake graphite.
4. The preparation method according to claim 3, characterized in that: The flake graphite has a diameter of 1-5 μm.
5. The preparation method according to claim 1, characterized in that: The graphite and SiO x The mass ratio of the particles is (1-3):
1.
6. The preparation method according to claim 1, characterized in that: The conductive polymer fiber includes any one of polyaniline fiber, polypyrrole fiber or polythiophene fiber, or a combination of at least two thereof.
7. The preparation method according to claim 1, characterized in that: The conductive polymer nanofibers and SiO x The mass ratio of the particles is (1-1.5):
1.
8. The preparation method according to claim 1, characterized in that: The lithium-containing compound is selected from any one of lithium oxide, lithium hydroxide or lithium salt, or a combination of at least two thereof.
9. The preparation method according to claim 8, characterized in that: The lithium-containing compound is a lithium salt.
10. The preparation method according to claim 8, characterized in that: The lithium salt includes any one of lithium carbonate, lithium acetate, lithium chloride, phenyl lithium or naphthyl lithium, or a combination of at least two thereof.
11. The preparation method according to claim 8, characterized in that: The median particle size of the lithium salt is 100-500 nm.
12. The preparation method according to claim 1, characterized in that: The lithium-containing compound and SiO x The mass ratio of the particles is (0.3-1.5):
1.
13. The preparation method according to claim 1 or 2, characterized in that: The mixing method in step (1) includes wet mixing.
14. The preparation method according to claim 13, characterized in that: The solvent for the wet mixing is an organic solvent.
15. The preparation method according to claim 14, characterized in that: The organic solvent includes ethanol and / or isopropanol.
16. The preparation method according to claim 1, characterized in that: The granulation method in step (1) is spray drying.
17. The preparation method according to claim 1, characterized in that: The granulation temperature in step (1) is 60-110°C.
18. The preparation method according to claim 1, characterized in that: The sintering temperature in step (2) is 700-1000°C.
19. The preparation method according to claim 1, characterized in that: The sintering time in step (2) is 1-8h.
20. The preparation method according to claim 19, characterized in that: The sintering time in step (2) is 2-6 hours.
21. The preparation method according to claim 1, characterized in that: The sintering in step (2) is carried out in a protective atmosphere.
22. The preparation method according to claim 21, characterized in that: The protective atmosphere includes a nitrogen atmosphere and / or an argon atmosphere.
23. The preparation method according to claim 1, characterized in that: The method for setting the carbon layer in step (3) includes a gas phase carbon coating method, a liquid phase carbon coating method or a solid phase carbon coating method.
24. The preparation method according to claim 23, characterized in that: The carbon source of the gas phase carbon coating method includes any one of acetylene, ethylene, methane, ethane, propane or butane, or a combination of at least two of them.
25. The preparation method according to claim 23, characterized in that: The coating temperature of the gas phase carbon coating method is 700-1200°C.
26. The preparation method according to claim 23, characterized in that: The coating time of the gas phase carbon coating method is 0.5-3h.
27. The preparation method according to claim 1, characterized in that: The mass percentage of the carbon layer in the pre-lithiated silicon oxygen carbon material is 1-10%.
28. The preparation method according to claim 27, characterized in that: The mass percentage of the carbon layer in the pre-lithiated silicon-oxygen-carbon material is 3-8%.
29. A pre-lithiated silicon-oxygen-carbon material, characterized in that: The pre-lithiated silicon oxygen carbon material is prepared by the preparation method according to any one of claims 1-28.
30. The pre-lithiated silicon-oxygen-carbon material according to claim 29, characterized in that: The pre-lithiated silicon-oxygen-carbon material is in the form of spherical particles.
31. The pre-lithiated silicon-oxygen-carbon material according to claim 29, characterized in that The median particle size of the pre-lithiated silicon oxygen carbon material is 8-20 μm.
32. A silicon oxygen carbon-graphite composite material, characterized in that: The silicon-oxygen-carbon-graphite composite material comprises a combination of the pre-lithiated silicon-oxygen-carbon material and graphite as described in any one of claims 29 to 31; the graphite is graphite secondary particles, and the ratio of the median particle size of the pre-lithiated silicon-oxygen-carbon material to the graphite secondary particles is 1:(1.25-2.5).
33. The silicon oxygen carbon-graphite composite material according to claim 32, characterized in that: The median particle size of the graphite secondary particles is 15-35 μm.
34. The silicon oxygen carbon-graphite composite material according to claim 32, characterized in that: The mass ratio of the pre-lithiated silicon oxygen carbon material to graphite is 1:(1-3).
35. The silicon oxygen carbon-graphite composite material according to claim 32, characterized in that: The specific surface area of the silicon oxygen carbon-graphite composite material is 1.8-2.5m 2 / g.
36. The silicon oxygen carbon-graphite composite material according to claim 32, characterized in that: The powder resistivity of the silicon oxygen carbon-graphite composite material is 1.0-20.0 μΩ / cm.
37. A method for preparing the silicon oxygen carbon-graphite composite material according to any one of claims 32 to 36, characterized in that: The preparation method comprises: uniformly mixing the pre-lithiated silicon oxygen carbon material and graphite to obtain the silicon oxygen carbon-graphite composite material.
38. A negative electrode active material, characterized in that The negative electrode active material comprises the silicon oxygen carbon-graphite composite material as described in any one of claims 32 to 36.
39. A lithium ion battery, characterized in that: The lithium-ion battery comprises a negative electrode, wherein the negative electrode comprises at least one of the silicon-oxygen-carbon-graphite composite material according to any one of claims 32 to 36 and the negative electrode active material according to claim 38.
Citation Information
Patent Citations
Preparation method of artificial graphite and SiO-based silicon-carbon composite cathode material
CN109686957A
Preparation method of high-performance silicon carbon-graphite composite negative electrode material for lithium ion batteries
CN110844908A
Silicon-based negative electrode material and preparation method thereof, negative electrode and lithium ion battery
CN112952054A
High-first-effect and high-magnification silicon-based negative electrode material and preparation method thereof
CN113422013A
Particulates of conducting polymer network-protected anode active material particles for lithium-ion batteries
US20200335792A1